Peripheral Ulcerative Keratitis in Relapsing Polychondritis: An Ophthalmic Challenge - Shah, Sangeeta; Lavaju, Poonam; Chaudhary, Santosh; Gupta, Namrata (Journal of BP Koirala Institute of Health Sciences, 2022)
Peripheral ulcerative keratitis (PUK) is an inflammatory condition leading to ocular morbidity. It can be associated with underlying autoimmune diseases which often goes undetected if the ocular manifestation precedes the systemic manifestation. The objective of this case report is to highlight that, the management of such entity is challenging. We present a case of a 36-year- old female with diminution of vision, PUK with necrotizing scleritis in both the eyes for which she was on regular treatment. Along with medications, she underwent multilayered amniotic membrane transplantation and scleral graft. Later on she developed tracheal stenosis and polychondritis for which she underwent tracheostomy. The ocular presentation of relapsing polychondritis can precede the systemic manifestations which may lead to delay in diagnosis and management of the disease. Unless the underlying disease is addressed, ocular morbidity progresses regardless the ocular treatment.